Impact of the implementation of the guidelines of the "Colombia buying efficient" in the hiring process in the selection mode the minimum amount Invima (2014)
In the search for a significant improvement in the process of contracting and purchasing specifically select mode small claims developed at the National Institute of Food and Drug Monitoring - INVIMA, the approach of conducting this research project was created with the purpose to identify the impact that can occur INVIMA to go through a process of implementing the guidelines of "Colombia Efficient Buy" program in their buying process performing a contrast of how the current process with the proposals of the Government program. With what is to establish a number of changes to the recruitment process and buy used today and thus able to clearly identify how, why and for the changes to be implemented in search of a significant improvement in the process of INVIMA contracting and procurement.